Effectiveness of training in evidence-based medicine skills for healthcare professionals: a systematic review - Hecht, Lars; Buhse, Susanne; Meyer, Gabriele (BMC medical education, 2016)
Background Basic skills in evidence-based medicine (EbM) are indispensable for healthcare professionals to promote consumer-centred, evidence-based treatment. EbM training courses are complex interventions – a fact that has not been methodologically reflected by previous systematic reviews. This review evaluates the effects of EbM training for healthcare professionals as well as the quality of reporting of such training interventions. Methods We searched PubMed, EMBASE, CINAHL, Cochrane Library, ERIC, Campbell Library and PsycINFO up to 9/2014. Randomised controlled trials, controlled clinical trials as well as before-after trials were included. Authors were contacted in order to obtain missing data. Two independent reviewers extracted data and assessed risk of bias. Results We reviewed 14.507 articles; n = 61 appeared potentially eligible; n = 13 involving 1,120 participants were included. EbM training shows some impact on knowledge and skills, whereas the impact on practical EbM application remains unclear. Risk of bias of included trials raises uncertainty about the effects. Description of complex interventions was poor. Conclusions EbM training has some positive effects on knowledge and skills of healthcare professionals. Appropriate methods for development, piloting, evaluation, reporting and implementation of the training should be applied.